The Little Data Book 2007 - World Bank (Washington, DC, 2012)
The Little Data Book (LDB) 2007 is a pocket edition of World Development Indicators (WDI) 2007. It is intended as a quick reference for users of the WDI 2007 book and CD-ROM and WDI online, electronic subscription database. Together, they cover more than 800 indicators and span 40 years. The 208 pages of country tables in the LDB present the latest available data for World Bank member countries and other economies with populations of more than 30,000. The 14 summary pages cover aggregate data for regional and income groups. The data in this book are for 1990, 2000, and 2005 or the most recent year unless otherwise noted in the glossary: i) growth rates are proportional changes from the previous year unless otherwise noted; ii) regional aggregates include data for low- and middle-income economies only; and iii) figures in italics indicate data for years or periods other than those specified. Data are shown for economies with populations greater than 30,000 or for smaller economies if they are members of the World Bank. The term country (used interchangeably with economy) does not imply political independence or official recognition by the World Bank but refers to any economy for which the authorities report separate social or economic statistics.